KARAKTERISTIK HIDROOSEANOGRAFI DIPERAIRAN PESISIR KABUPATEN AGAM - muarif, muarif (Jurnal Mina Sains, 2018)
The research objectives to explore the characteristic of hydrooceanography in coastal of Agam Regency. The observations parameters included physical aspecs such as bathymetric, tide, wave, water current, Transparancy, and temperature; and so chemical aspecs such as pH, salinity, dissolved oxygen, and COD. Hydrooseanographic characteristics on Agam Regency coastal described the bathymetry was shallow to deep , high wave, high tidal range, water currents dependent on season, and water quality were in good criteria to life support of aquatic biota.Â Key words: Hydrooceanography, wave, tidal, water quality